Memoirs of the Court of St. Cloud (Being secret letters from a gentleman at Paris to a nobleman in London) $1 (BVolume 7s - Goldsmith, Lewis, 1763?-1846 (Salt Lake City, UT : Project Gutenberg, 2004)
"Memoirs of the Court of St. Cloud" by Lewis Goldsmith is a historical account written in the early 19th century. The work comprises a series of letters from a gentleman residing in Paris to a nobleman in London, detailing the intricacies of the political landscape during Napoleon's rise to power. The letters offer insight into the political machinations, diplomatic relations, and the lives of various dignitaries associated with the French court, showcasing the tensions and intrigues present in this tumultuous era of history. At the start of the memoirs, the correspondent addresses the reactions of different European powers to Napoleon's ambitions, emphasizing the Russian cabinet's prudent diplomacy compared to the often tumultuous interactions at the French court. Key figures such as Count Woronzow and Prince Czartorinsky are introduced, highlighting their roles in maintaining Russian dignity amidst upstart challenges from the French leadership. The initial letters lay the groundwork for the complexities of diplomacy, setting the stage for ongoing commentary on Napoleon and the evolving European political scene, with a particular focus on the adverse societal conditions faced by the French populace under Bonaparte's rule. (This is an automatically generated summary.)
Release date is 2004-12-04
Produced by David Widger
Keywords: Napoleon I, Emperor of the French, 1769-1821; France -- Court and courtiers; France -- History -- Consulate and First Empire, 1799-1815; France -- Kings and rulers -- Biography